Passive optical network architecture based on waveguide grating routing. - Banerjee, D. (IEEE Journal on selected areas in communications)
We explore an optical network architecture which employs dense wavelength division multiplexing (WDM) technology and passive waveguide grating routers (WGRs) to establish a virtual topology based on lightpath communication. We examine the motivation and the technical challenges involved in this approach, propose and examine the characteristics of a network design algorithm, and provide some illustrative performance results